2021
DOI: 10.3389/fpsyg.2021.643759
|View full text |Cite
|
Sign up to set email alerts
|

Altruism, Environmental Concerns, and Pro-environmental Behaviors of Urban Residents: A Case Study in a Typical Chinese City

Abstract: To investigate the relationships between altruism, environmental concerns, and ordinary people's pro-environmental behaviors that go beyond self-interested NIMBY-ism, we examined measurements of altruism and environmental concerns in a Chinese context and developed a scale that measured people's pro-environmental behaviors at the individual, organizational, and policy level. We then conducted a tailor-made, face-to-face survey (N = 603) and found, first, that old age, gender (being a woman), party affiliation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 84 publications
2
22
1
Order By: Relevance
“…The VBN theory is frequently used to explore individuals’ differences in various social behavior. Egoistic, altruistic, and biospheric value orientations that previous studies typically use to discuss distinct environmental behavior also align with the belief in the VBN theory ( Dietz et al, 2002 ; De Groot and Steg, 2007 ; Xu et al, 2021 ). Besides, the theory of green purchase behavior that was established recently admits the role of the VBN theory in exploring green consumption behavior as well ( Han, 2020 ).…”
Section: Introductionmentioning
confidence: 54%
“…The VBN theory is frequently used to explore individuals’ differences in various social behavior. Egoistic, altruistic, and biospheric value orientations that previous studies typically use to discuss distinct environmental behavior also align with the belief in the VBN theory ( Dietz et al, 2002 ; De Groot and Steg, 2007 ; Xu et al, 2021 ). Besides, the theory of green purchase behavior that was established recently admits the role of the VBN theory in exploring green consumption behavior as well ( Han, 2020 ).…”
Section: Introductionmentioning
confidence: 54%
“…According to VBN theory, as proposed by Stern et al (1999) , Stern (2000) proenvironmental behavior is driven by individual values, and proenvironmental intention or behavior is the result of the joint influence of ALVs and EGVs ( Le et al, 2019 ; Yang and Zhang, 2021 ). Individuals with ALVs focus on human interests and care about the long-term interests of others and society ( Xu et al, 2021 ). Individuals with EGVs are more concerned with their own interests and self-improvement and avoid possible harm to themselves due to changes in the external environment ( Kiatkawsin and Han, 2017 ) and attempt to influence and control others to achieve their personal goals.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Values have orientation, recognition, and motivation functions for individual daily behavior ( Stern et al, 1999 ; Stern, 2000 ; Lan et al, 2009 ; Han, 2015 ) and guide and regulate the generation and choice of behaviors ( Uddin et al, 2021 ). Values are also stable so they can better predict and explain the generation of behavioral intention ( Xu et al, 2021 ). In the original model and the improved model of the value-belief-norm (VBN) theory, altruistic values (ALVs) and egoistic values (EGVs) reflect well an individual’s dual appeals.…”
Section: Introductionmentioning
confidence: 99%
“…Given that authenticity increases morality, we propose that authenticity can positively predict PEB and the intention to conduct PEB, because PEB also has moral implications (e.g., Schultz, 2001 ; Haidt and Kesebir, 2010 ; Markowitz and Shariff, 2012 ; Xu et al, 2021 ; for a review, see Nolan and Scultz, 2015 ). For example, environment protection has been assumed by researchers to be an exemplary value of the universalism, which is one of the 10 basic human values ( Schwartz, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other works also showed that some personal values, e.g., biospheric (valuing the welfare of natural environment) and altruistic (valuing the wellness of other people) ones, are relevant in predicting PEB ( Stern and Dietz, 1994 ; Bouman et al, 2018 ). Among lay people, PEB is positively correlated with prosocial behavior (e.g., Neaman et al, 2018 ; Xu et al, 2021 ), and can be perceived as a signal of the actor’s moral characteristics ( Vesely et al, 2020 ). Meanwhile, individuals who endorse self-transcendent values (e.g., environmentalism) are more likely to feel moral obligations toward the environment ( Karp, 1996 ; Schultz and Zelezny, 1998 ; Feinberg and Willer, 2013 ).…”
Section: Introductionmentioning
confidence: 99%